Promoting prospective teachers’ conceptual knowledge through web-based blended learning - Yurniwati, Yurniwati; Yarmi, Gusti (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
Fractions remain a difficult concept for students at the elementary level. On that ground, prospective teachers need to develop the conceptual knowledge to have a deep understanding of the concept and how the concepts are related to each other. Furthermore, they must be able to explain the concepts through media in the form of concrete objects or images to help students grasp the whole concept of fractions. This research investigates the effect of web-based blended learning on the development of Conceptual Knowledge of prospective teachers. Webbased blended learning is a combination of online learning and face to face classroom group discussion. Prospective teachers use Edmodo as the learning management system that contains various learning resources such as videos, documents, and students’ assignments in the form of Google Forms. This study design is a non-experimental post-test. The data obtained by using open tests and analyzed descriptively. Participants are prospective teachers who enrolled in the Teaching Arithmetic course in the 7th semester of the 2018/2019 academic year at the Department of Primary School Teacher Training, Universitas Negeri Jakarta, Indonesia. This study found web-based blending learning is an effective learning system to develop prospective mathematics elementary teachers’ conceptual abilities of fractions. It is recommended that this learning system be included in the prospective teachers’ Education module.